1999
DOI: 10.1080/02688699944195
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers of brain damage and outcome prediction in patients after severe head injury

Abstract: The objective of the study was to investigate the validity of outcome prediction after severe head injury using serum levels of S-100B protein and neuron specific enolase. Eighty-two patients with severe head injury were included in this prospective study. Venous blood samples were taken after admission and every 24 h for a maximum of 10 consecutive days. For values of S-100 from 0 to 2.5 micrograms/l, and for values of NSE from 0 to 100 micrograms/l the sensitivity and specificity of incremental values as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(81 citation statements)
references
References 21 publications
6
67
1
6
Order By: Relevance
“…Alternatively, several proteins synthesized in astroglial cells or neurons have been proposed as biomarkers of cell damage in the CNS, but insufficient evidence is currently available to justify their routine clinical use (Ingebrigtsen and Romner, 2002;Lyeth et al, 1993;Papa et al, 2008;Raabe and Seifert, 1999;Raabe et al,. 1999a).…”
mentioning
confidence: 99%
“…Alternatively, several proteins synthesized in astroglial cells or neurons have been proposed as biomarkers of cell damage in the CNS, but insufficient evidence is currently available to justify their routine clinical use (Ingebrigtsen and Romner, 2002;Lyeth et al, 1993;Papa et al, 2008;Raabe and Seifert, 1999;Raabe et al,. 1999a).…”
mentioning
confidence: 99%
“…Previous research has demonstrated that S-100β is superior to NSE in predicting the outcome status of both mild [20,21] and severe TBI subjects [22]. Wunderlich et al [23] showed that serum S-100β levels in acute stroke patients were predictive of neurological outcome at discharge and that serum NSE levels or lesion volumes obtained from CT scans did not add predictive value after adjusting for S-100β concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Glasgow Outcome Scale), kurios 1, 2 ir 3 reikšmės priskiriamos prie nepageidaujamų baigčių. 1999 metais Raabe su bendraautoriais nustatė stiprią koreliaciją su nepageidaujamomis baigtimis, kai serumo S100B koncentracija yra 2,5 μg/l ir daugiau (14,15). Tais pačiais metais Woertgen su kolegomis paskelbė, kad S100B koncentracijai serume esant 2 μg/l ir daugiau stebima stipri koreliacija su nepageidaujamomis baigtimis (35).…”
Section: Tyrimo Objektas Ir Metodasunclassified